2021
DOI: 10.1002/pen.25642
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity decrease by interfacial slippage between immiscible polymers

Abstract: The rheological behavior under pressure‐driven shear flow was studied using binary blends with a sea‐island structure. The addition of a low‐viscosity dispersion having a high interfacial tension with the continuous phase greatly reduces the shear viscosity, for example, the addition of atactic polystyrene (PS) with a low viscosity to isotactic polypropylene (PP) and the addition of PP with a low viscosity to PS. The interfacial slippage occurs because of the poor adhesive strength with the enlarged interfacia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In the skin region, i.e., high shear rate region, LDPE droplets were deformed greatly to the flow direction. As a result, a large interfacial area was provided, which pronounced the interfacial slippage between PC and LDPE, as revealed in previous studies [ 8 , 9 , 16 ]. In contrast, spherical LDPE droplets were observed in the core.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…In the skin region, i.e., high shear rate region, LDPE droplets were deformed greatly to the flow direction. As a result, a large interfacial area was provided, which pronounced the interfacial slippage between PC and LDPE, as revealed in previous studies [ 8 , 9 , 16 ]. In contrast, spherical LDPE droplets were observed in the core.…”
Section: Resultssupporting
confidence: 63%
“…When the interfacial tension is not so high, this leads to a thick interfacial thickness, and shear viscosity of the blend does not decrease greatly. Such a phenomenon was confirmed for the blends of polypropylene (PP) as a continuous phase and ethylene-α-olefin copolymer as dispersion [ 16 ].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It was found that the addition of PVAL decreased the shear viscosity greatly. When an immiscible polymer having low viscosity is dispersed, the apparent shear viscosity decreased greatly due to the slippage at the enlarged interfacial area. Interfacial slippage occurs for most immiscible polymer pairs because the interfacial thickness is not thick enough to have good adhesion in general. Considering the interfacial tension between PLA and PVAL (1.64 mN/m), the viscosity decrease at the present system was also attributed to the interfacial slippage.…”
Section: Resultsmentioning
confidence: 79%
“…Issues of interest regarding the interface rheology of polymeric flows include the drag friction of a droplet [ 1 , 2 ], the coalescence kinetics of droplets in immiscible blends and emulsions [ 3 ], the viscosity reduction in polymer blends [ 4 , 5 ] and emulsions [ 6 ] by interfacial slip, multilayer melt flow in coextrusion processing [ 7 ], adhesion properties in relation to the effect of melt rheological processing [ 8 ], and the interface formation in multi-material 3D printing [ 9 ]. Understanding these phenomena requires the characterization of not only the bulk rheology of the components but also of the interface rheology.…”
Section: Introductionmentioning
confidence: 99%